Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2020)
A dataset containing 7916 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "Continent is Africa", "Continent is Antarctica", "Continent is Asia", "Continent is Oceania", "Continent is Europe", "Continent is North America", "Continent is South America" ] }, "Month is July", "HasCoordinate is true", "TaxonKey is Rhododendron L.", "HasGeospatialIssue is false" ] } The dataset includes 7916 records from 62 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0062964-200221144449610/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences